2007
DOI: 10.1007/s00249-007-0227-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of divalent cations on the structure of the antibiotic daptomycin

Abstract: Daptomycin, a cyclic anionic lipopeptide antibiotic, whose three-dimensional structure was recently solved using solution state NMR (Ball et al. 2004; Jung et al. 2004; Rotondi and Gierasch 2005), requires calcium for function. To date, the exact nature of the interaction between divalent cations, such as Ca(2+) or Mg(2+), has not been fully characterized. It has, however, been suggested that addition of Ca(2+) to daptomycin in a 1:1 molar ratio induces aggregation. Moreover, it has been suggested that certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
96
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 45 publications
10
96
0
Order By: Relevance
“…They also determined the structure of daptomycin (2 mM) in the presence of 5 mM MgCl 2 . 37 No line broadening was observed, and the obtained structure closely resembled their previously reported apo-daptomycin structure. 42 Ball et al also reported the structure of Ca 2+ -bound daptomycin using an 0.8 mM solution of daptomycin at pH 5.3.…”
Section: Solution Structure Of Calcium-bound Daptomycinsupporting
confidence: 86%
See 1 more Smart Citation
“…They also determined the structure of daptomycin (2 mM) in the presence of 5 mM MgCl 2 . 37 No line broadening was observed, and the obtained structure closely resembled their previously reported apo-daptomycin structure. 42 Ball et al also reported the structure of Ca 2+ -bound daptomycin using an 0.8 mM solution of daptomycin at pH 5.3.…”
Section: Solution Structure Of Calcium-bound Daptomycinsupporting
confidence: 86%
“…Realizing that daptomycin aggregation may have affected their results, Straus et al re-examined their Ca 2+ -bound daptomycin structure in detail. 37 Molecular dynamics (MD) simulations suggested that the conformational change in daptomycin upon binding Ca 2+ might not be as significant as originally proposed. It was concluded that none of the Ca 2+ -bound daptomycin models tested in the MD simulations were consistent with the NOE restraints reported earlier, and that the previously reported NOE restraints between residues Asp (3) and Ala (8) were intermolecular and should not been included during structure refinement.…”
Section: Solution Structure Of Calcium-bound Daptomycinmentioning
confidence: 87%
“…in the presence of high concentrations of Ca 2+ [46][47][48]. With the Ca 2+ /daptomycin molar ratio at 1:1 under these conditions, oligomerization occurs, resulting in 14 to 16 monomers forming micelles [35,49,50]. The arrangement into micelles is not accompanied by a change in lipopeptide conformation, as originally proposed [36].…”
Section: Daptomycin and Derivativesmentioning
confidence: 61%
“…The anionic character of daptomycin is masked by its complexation with divalent cations such as Ca 2+ , enabling the lipopeptide to perturb bacterial membranes in a detergent-like manner, analogously to what has been suggested for cationic antimicrobial peptides [33][34][35].…”
Section: Daptomycin and Derivativesmentioning
confidence: 87%
“…The addition of one or more equivalents of Ca 2ϩ completely inverted the positive ellipticity at 230 nm in the absence of calcium. This effect has been interpreted as being due to a Ca 2ϩ -dependent change in structure (15,19) or daptomycin-mediated fusion of POPC-POPG liposomes in the presence of calcium (16) without a structural change (12).…”
mentioning
confidence: 99%